Evaluasi Hubungan Deviasi dan Energi terhadap Kestabilan Keluaran Berkas Elektron pada Pesawat LINAC Varian TrueBeam - Sakinah; Primasari Cahya Wardhani; Arie Chintya Martania; Nur Aini Fauziyah; Wahyu Dwi Lestari (Universitas Andalas, 2026)
This study aims to analyze the relationship between electron beam energy and electric charge, as well as the relationship between deviation and energy, to evaluate the output stability of the LINAC machine. Measurements were conducted at BPAFK Surabaya using a Varian TrueBeam LINAC at Hospital X, East Java. The study employed electron energies of 6 MeV, 9 MeV, 12 MeV, 16 MeV, and 18 MeV. The procedure included filling the water phantom with distilled water, setting the source-to-surface distance (SSD) to 100 cm with a radiation field size of 10 cm × 10 cm, and connecting the detector to the electrometer outside the LINAC room. Calibration was performed at the reference depth (Zref) based on the R₅₀ value from the Percentage Depth Dose (PDD) table according to the IAEA TRS-398 standard. Measurements were repeated five times with voltage variations of +300 V, −300 V, and +75 V. The results showed that the maximum electric charge occurred at 12 MeV at a depth of 2.96 cm, while the highest deviation, −0.15%, was observed at 16 MeV—still within the ±2% tolerance limit. Therefore, the LINAC machine is considered stable and suitable for use in radiotherapy.